Mechanical properties of carbon-aramid hybrid fiber-reinforced epoxy/poly(vinyl butyral) composites - ÇAKIR, MUSTAFA; AKIN, EMRE (My University, 2023)
Currently, it is important to manufacture fiber-reinforced epoxy matrix composites with high impact resistance besides their high strength and modulus values for industries such as automotive, aerospace, and aviation due to the brittle structure of epoxy. In this regard, we found the attractive results of the 0.5 wt% poly(vinyl butyral) (PVB)-containing epoxy blend in terms of strength, Young\"s modulus, and impact resistance. These results substantially motivated us to manufacture fiber-reinforced advanced epoxy/PVB matrix composites with 30–60 vol% carbon-aramid fiber ratios. Flexural (three-point bending) and tensile tests were performed to obtain strength and modulus values by measuring the force required to break the fiber-reinforced composite specimens and elongation at break points. Interlaminar shear strength tests were performed by the short beam bending method by measuring the resistance of the composite to delamination. The Charpy impact test was used to measure the energy absorbed during crack formation and fracture propagation. The composites with PVB were generally superior to those without PVB (EPCs). Two types of findings were observed. First, PVB increased the tensile and flexural strength values substantially for the 30 and 40 vol% ratios, but the modulus values slightly decreased. Second, PVB also substantially increased the modulus values for the 50 vol% ratio besides the strength values. It was thought that this result could be attributed to the increase in the compatibility of the fiber/matrix for the 50 vol% ratio. These decreases for EPCs could be derived from the micro-cracks and weaker interface between fiber and matrix.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, CERAMICS; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Seramik ve Kompozitler; Fizik Bilimleri; Genel Kimya; Polimerler ve Plastikler; Malzeme Kimyası; Ceramics and Composites; Physical Sciences; General Chemistry; Polymers and Plastics; Materials Chemistry; carbon-aramid hybrid fibers; epoxy; PVB blend matrix; fiber-reinforced composites; poly(vinyl butyral); FRACTURE-TOUGHNESS; PVB/FE3O4; epoxy/PVB blend matrix; carbon-aramid hybrid fibers; epoxy/PVB blend matrix; fiber-reinforced composites; poly (vinyl butyral)